Preventing intimate partner violence by engaging men: Evidence from Unite for Better Life in Ethiopia - Salgado, Isabela; Leight, Jessica; Sharma, Vandana (Massachusetts Institute of Technology, 2020)
Globally, 30 percent of women will experience physical and/or sexual violence by an intimate partner in their lifetime. The well-documented health consequences of intimate partner violence (IPV) include injuries, unintended pregnancies, sexually transmitted infections, long-lasting mental illnesses, and, in the most extreme cases, death. IPV survivors are also subject to economic and social costs, such as reductions in income and productivity and social stigma.